LEVEL OF FATIGUE AMONG MALE PATIENTS WITH CANCER - I Komang Leo Triandana Arizona; Tintin Sukartini; Ferry Efendi (International Journal of Nursing and Health Services (IJNHS), 2019)
Cancer-related fatigue (CRF) is one of the symptoms commonly experienced by cancer patients and has an impact on decreasing quality of life. The study aimed to explore the characteristics of cancer patients who experience cancer-related fatigue. The study involved 15 cancer patients using purposive sampling. The research instrument used a questionnaire characteristic of the research subjects and the Brief Fatigue Inventory. Descriptive data analysis using percentages and numbers. The results showed that most cancer patients experienced moderate fatigue, in the age range of the early elderly, stage III and received combination therapy. Fatigue in cancer patients is a symptom caused by multi factors. Cancer stage and type of treatment is one aspect that appears in the severity of perceived fatigue. CRF can occur in all phases of the disease, age, and type of treatment. Patient education about CRF needs to be done especially related to the management of fatigue that can be done both before and after treatment. Keywords: cancer-related fatigue, weakness